Vedic astrological factors for human immunodeficiency virus transmission within male individuals with sexual orientation as homosexual - Raj, Dipesh (Dharmakirti : International Journal of Religion, Mind and Science, 2024)
Background: For almost more than 70 years, the modern science had labeled homosexuality as a mental disorder and was part of DSM (Diagnostic and Statistical Manual of Mental Disorders) until the fifth edition was released in the year 2013 and homosexuality was removed from the mental disorder list. Despite of the removal of homosexuality along with all kind of sexual orientation from mental disorder, it is still being considered taboo in the society. From Sanatana Dharma perspective, homosexuality is very well mentioned in multiple scriptures. In Vedic Astrology as well, this homosexuality along with diseases due to sexual intercourse is being described. In this modern era, one of the most common disease due to sexual intercourse is HIV. Although, HIV is considered relatively new transmission due to its first scientific mention in the late twentieth century, the symptoms and overall nature of this disease is clearly described in Vedic Astrology. Finding: This research paper is an extension of the existing research paper in the field of Vedic Astrology especially in the field of Vedic Astrology focusing on HIV transmission. A total of 314 HIV positive samples was collected from 18 countries selected from Asia, Europe, North America, South America, Africa as well as Australia in order to have a coverage of all the continents. All these HIV positive people belong to LGBT community, to be very specific Gay (homosexuals) and have been identified as HIV transmission due to anal intercourse with another Gay partner. The Astrological Natal Chart were analyzed for all these 314 samples against the KIRAN sutra (5 thumb rules) to find the possibility of HIV based on the sutras i.e. rules. Out of 314 samples, 310 charts fit the criteria (KIRA sutra) mentioned in the KIRAN sutra for HIV transmission. 4 samples were not checked against the criteria (N) due to insufficient Nakshatra-Pada i.e. Constellation-Phase coverage along with the complex nature of the Nakshatra sutra i.e. N sutra of KIRAN sutra. The result indicates that the KIRAN sutra is very effective sutra even to identify the HIV transmission from male-to-male partner with an accuracy of 98.73% (310 cases out of 314 cases) using only 4 sutras i.e. KIRA. Conclusion: The research is an effort to raise awareness and to help males with homosexual orientation to identify whether they are highly prone to HIV or not using their Vedic Astrological Natal Chart so that they can take preventive action. A new yoga i.e. Samalaingika Yauna Sankramaṇa Yoga is being introduced in the field of Medical Astrology focusing on males with sexual orientation as homosexual, commonly known as Gay in LGBT community in order to support Gays living a HIV free life without judging their sexual orientation. Novelty/Originality of this article: This study introduces the application of the KIRAN sutra from Vedic Astrology as a predictive method for assessing HIV transmission risk in homosexual men, achieving an accuracy rate of 98.73%, along with the introduction of a new configuration, Samalaingika Yauna Sankramaṇa Yoga.